Exploratory and Confirmatory Factor Analyses of the Short Grit Scale (Grit-S) for Malaysian Undergraduate Students - Tan, Chee-Seng; Low, Su Rou; Chong, Hoi Yan; Chong, Shue Ling; Ong, Anna Wen-Huey; Siah, Poh Chua; Phang, Shiau Fen; Ong, Zhi Qi; Tan, Wei Hong; Wong, Jean Ann; Lew, Wei Him (Makara Human Behavior Studies in Asia, 2019)
The 8-item Short Grit Scale (Grit-S; Duckworth & Quinn, 2009) is a measure of the two aspects of grit: consistency of interests and perseverance of effort. While the majority of the past studies supported the two-factor model, some found cultural differences. Two studies were carried out to test the factor structure of the Grit-S in a sample of Malaysian undergraduate students (total N = 1109). Exploratory factor analysis (Study 1) revealed two factors. Item 2 for perseverance subscale was removed due to unsatisfactory factor loading. Further analysis of the seven items supported the two-factor model. Confirmatory factor analyses (Study 2) supported the superiority of the two correlated-factor model with 7 items. Moreover, the consistency and perseverance scores showed acceptable internal consistency. The current research contributes to the literature by lending further support to the theoretical two-factor structure of the Grit-S and revealing potential cultural differences in the items. Future studies are thus recommended to address these cultural differences and confirm the usability of the 7-item Grit-S in the Malaysian context